ABORDAREA SIMPLIFICATĂ FAŢĂ DE ESTIMAREA RISCULUI DE CREDITARE ÎN ACTIVITATEA BANCARĂ - Bunescu, Gheorghe (CEP USM, 2008)
Credit risk modeling is one of the most important components of the modern risk-management system. It takes the central part in the International Convergence of Capital Measurement and Capital Standards (a revised framework) published by the Basel Committee on Banking Supervision in June 2004. In spite of the significant theoretical achievements in this field, aspects, related to the application of the risk -management models in the pract ical commercial banks activity, are still pressing nowadays. A simplified a pproach to the estimation of the credit risk assumed by a bank is described in this work. It is based on the internal credit statistics, can be realized in the condition of the transition economy and can be also used for the purpose of scenarios analysis.
Keywords: riscuri bancare